The Effectiveness of Picture Letter Card Media in Enhancing Early Reading Skills: An Experimental Study of First-Grade Elementary Students - Indriani, Nur Fahmi; Amaliyah, Nurhadifah; Khaedar, Muh.; Fatimah, Waddi (Papanda Publisher, 2025)
Early reading skills constitute fundamental competencies for academic success and societal participation, yet significant proportions of elementary students encounter substantial barriers in mastering these critical abilities. This study investigated the effectiveness of picture letter card media on early reading learning for lower-grade elementary students. An experimental study with quantitative approach was conducted at SD Inpres Tala-tala, involving 23 first-grade students (13 males, 10 females) selected through saturation sampling. The intervention comprised six sessions: one pretest, four picture letter card treatment sessions, and one posttest. Data collection utilized reading ability tests, observation sheets, and documentation. Statistical analysis employed descriptive statistics and paired-samples t-tests using SPSS, with preliminary normality and homogeneity testing. Teacher implementation quality improved progressively from 2.5 to 3.8 (average 3.2, good category), while student engagement increased from 1.6 to 3.7 (average 2.8, good category). Reading performance demonstrated remarkable improvement from pretest mean of 34.78 to posttest mean of 86.9. Score distribution shifted dramatically, with 91% of students achieving good or very good performance levels in posttest compared to 0% in pretest. Statistical analysis revealed significant differences (p = 0.000 < 0.05), with normality (p = 0.083) and homogeneity (p = 0.680) assumptions satisfied. The substantial 150% improvement validates picture letter card media's effectiveness in addressing foundational literacy challenges. Results align with multimedia learning theory and previous visual media research, demonstrating successful integration of pedagogical content knowledge with accessible educational technology.